CHALLENGES AND EFFECTIVENESS: TEACHER AND STUDENT PERCEPTIONS OF FORMATIVE ASSESSMENT PRACTICE: CASE STUDY OBEKKHAM SECONDARY SCHOOL - Seng, Sophea; Reth, Phearun; Kun, Chanvey; Srieng, Kimsron; Mom, Sopheap (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
This study explores the challenges and effectiveness of formative assessment practices from the perspectives of teachers and students at Obekkham Secondary School to improve teaching and learning outcomes. The research employed a quantitative approach, using structured questionnaires to gather data from 24 science teachers and 700 students across grades 7 to 9 (using the Taro Yamane method). This research highlights the urgency of addressing the practices at the secondary level. The study focused on implementing formative assessments, feedback, and alignment with curriculum objectives. The findings indicate that formative assessments positively influence student motivation, engagement, and performance. However, challenges such as time constraints, inadequate training, and difficulties in adapting assessments to diverse learner needs exist. These results show the importance of immediate professional development for teachers and the adoption of adaptive strategies to integrate formative assessment practices into a more effective and inclusive secondary education system.